A new species of Boethella Bennett, 2003 (Hymenoptera: Ichneumonidae: Tryphoninae) from Brazil, redescription of the genus and a key to world species - Ferreira, João Pascoal Da Silva; Onody, Helena Carolina; Bennett, Andrew Michael Reeve; Timóteo, Ferreira Manuel; Penteado-Dias, Angélica Maria (Zootaxa, 2020)
Boethella jatai sp. nov. is described from a savanna area in the southeast of Brazil. The genus is redescribed to include the new species and an identification key for world species is provided.